Ajuste de intensidad para el trasplante hematopoyético alogénico en leucemia aguda. - Sarmiento M, Mauricio; Bertin C, Pablo; Jara, Verónica; Ocqueteau T, Mauricio; Ramírez V, Pablo (Revista Médica de Chile, 2016)
Background: The intensity of conditioning chemotherapy and radiotherapy in hematopoietic stem cell transplantation (HSCT) varies according to several factors including the patient’s age, pre-existing conditions and performance status. Myeloablative conditioning (MA) increases transplant related mortality and reduces survival in older patients. Reduced intensity conditioning (RIC) is a good option for these patients. Aim: To report our experience with HSCT in patients of different ages with acute leukemia. Material and methods: Retrospective analysis of 115 allogeneic HSCT performed in patients with acute myeloid or lymphoblastic leukemia. Results: We analyzed the cohort of patients in groups according to age at transplantation: younger than 40 years (n = 74), 41 to 50 years (n = 25) and older than 51 years (n= 16). OS, DFS and relapse at five years were similar in both groups of patients younger than 50 years (OS 40 and 44% respectively, DFS 38 and 42% respectively and relapse 40% and 34% respectively, p = NS). Patients over 51 years had a five years OS of 12%. However when we analyzed those patients by date and conditioning we found that patients who were treated with MA regimens in the first decade of the transplant program (before 2000) had lower OS compared to those treated after 2000 with RIC (five years OS 49% and 12% respectively, p < 0.01). No significant differences in terms of OS, recurrence or incidence of graft-versus-host disease were found when comparing groups under 40 years, between 41 and 50 years and older than 51 years treated only with RIC. Conclusions: RIC provides the possibility of HSCT in older patients with rates comparable to those obtained in younger patients successfully treated with MA conditioning.